The Economics of the Public Option: Evidence from Local Pharmaceutical Markets - Atal, Juan Pablo; Cuesta, José Ignacio; González, Felipe; Otero, Cristóbal (American Economic Review, 2024)
We study the effects of competition by state-owned firms, leveraging the decentralized entry of public pharmacies to local markets in Chile. Public pharmacies sell the same drugs at a third of private pharmacy prices, because of stronger upstream bargaining and market power in the private sector, but are of lower quality. Public pharmacies induced market segmentation and price increases in the private sector, which benefited the switchers to the public option but harmed the stayers. The countrywide entry of public pharmacies would reduce yearly consumer drug expenditure by 1.6 percent. (JEL D22, I18, L32, L65, O14)